Phytoplankton Community Structure and Saprobic Index In Freshwater Fish Cultivation Ponds - Hapsari, Larasati Putri; Mayasari, Elistanti (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
Phytoplankton are unicellular algae plants found in marine and freshwater ecosystems. The presence of phytoplankton in waters plays an important role in the cultivation process. However, not all types of phytoplankton can have a good impact on cultivation ponds, this is because there are types of phytoplankton that are toxic and can cause death to the biota in the pond. This observation regarding phytoplankton aims to determine the structure of the phytoplankton community in cultivation ponds and determine the water quality in cultivation ponds through the saprobic coefficient value. The method used is a survey by determining sampling locations using the simple random sampling method. The data obtained were analyzed using the diversity index, dominance index, uniformity index and saprobic coefficient index. Observation results show that the Phytoplankton Community Structure in freshwater fish cultivation ponds at the Karawang Marine and Fisheries Polytechnic has 4 classes, namely Chlorophyceae (6 genera), Cyanophyceae (3 genera), Bacillariophyceae (6 genera) and Dinophyceae (2 genera) with abundance. Ranged from 7,500 cells/mL to 305 cells/mL. The diversity index shows moderate population stability with a high uniformity index and the absence of species dominance. The saprobity index shows values ranging from lightly to moderately polluted so that the cultivation ponds at the Karawang Marine and Fisheries Polytechnic are still classified as good and can be used for cultivation activities. However, it is necessary to always monitor and evaluate so that these conditions are maintained and do not become heavily polluted.